PRAKTIK POLITIK UANG (MONEY POLITIC) DALAM PEMILU (Studi Analisis Tinjauan Hukum Positif dan Hukum Islam): (Studi Analisis Tinjauan Hukum Positif dan Hukum Islam) - Janeko; Uzlah Wahidah (The Republic : Journal of Constitutional Law, 2024)
Money Politics is an attempt to influence other people by using material rewards or can be interpreted as buying and selling votes in the political process, power and the act of distributing money, whether personal or party property, to influence voters' votes ahead of the day of the general election. The practice of Money Politics is carried out by giving money, basic necessities including rice, oil and sugar to the public with the aim of attracting public sympathy so that they vote for the party concerned. This type of research is library research (Library Research is a data collection technique by conducting a review study of books, literature, notes and reports. Islamic law and law view money politics, that is, they both consider money politics in elections is haram or prohibited. Meanwhile, the difference is that in Islamic law and law, money politics is viewed as an act that is prohibited by the Shari'a and acts of money politics are included in the category of risywah, whereas in positive law, money politics is viewed as an act that violates the law. -laws governing elections. Money Politics is an attempt to influence other people by using material rewards or can be interpreted as buying and selling votes in the political process, power and the act of distributing money, whether personal or party property, to influence voters' votes ahead of the day of the general election. The practice of Money Politics is carried out by giving money, basic necessities including rice, oil and sugar to the public with the aim of attracting public sympathy so that they vote for the party concerned. This type of research is library research (Library Research is a data collection technique by conducting a review study of books, literature, notes and reports. Islamic law and law view money politics, that is, they both consider money politics in elections is haram or prohibited. Meanwhile, the difference is that in Islamic law and law, money politics is viewed as an act that is prohibited by the Shari'a and acts of money politics are included in the category of risywah, whereas in positive law, money politics is viewed as an act that violates the law. -laws governing elections.